The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1998
DOI: 10.1021/bp980072i
|View full text |Cite
|
Sign up to set email alerts
|

Hg2+ Removal by Genetically Engineered Escherichia coli in a Hollow Fiber Bioreactor

Abstract: Escherichia coli cells engineered to express an Hg2+ transport system and metallothionein accumulated Hg2+ effectively over a concentration range of 0.2-4 mg/L in batch systems. Bioaccumulation was selective against other metal ions and resistant to changes in ambient conditions such as pH, ionic strength, and the presence of common metal chelators or complexing agents (Chen, S.-L.; Wilson, D. B. Appl. Environ. Microbiol. 1997, 63, 2442-2445; Biodegradation 1997, 8, 97-103). Here we report the characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 15 publications
(18 reference statements)
0
26
0
Order By: Relevance
“…Mercury is a heavy metal with extreme toxicity, and, owing to its ability to biomagnify and its high residence time in the environment, it causes havoc for other living organisms as well as the ecosystem. Technologies for treating mercury-polluted environments have been a major concern over the last couple of decades (Williams and Silver, 1984;Nakamura et al, 1990;Brunke et al, 1993;Canstein et al, 1999;Canstein, 2000;Chang et al, 1997, Chen et al, 1998Essa et al, 2002;Wagner-Döbler, 2003;Deckwer et al, 2004). Common methods to remove Hg 21 from contaminated water are mostly based on sorption to materials such as ion exchange resins (Osteen and Bibler, 1991;Ritter and Bibler, 1992).…”
Section: Bioaccumulating Mercury-resistant Marine Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Mercury is a heavy metal with extreme toxicity, and, owing to its ability to biomagnify and its high residence time in the environment, it causes havoc for other living organisms as well as the ecosystem. Technologies for treating mercury-polluted environments have been a major concern over the last couple of decades (Williams and Silver, 1984;Nakamura et al, 1990;Brunke et al, 1993;Canstein et al, 1999;Canstein, 2000;Chang et al, 1997, Chen et al, 1998Essa et al, 2002;Wagner-Döbler, 2003;Deckwer et al, 2004). Common methods to remove Hg 21 from contaminated water are mostly based on sorption to materials such as ion exchange resins (Osteen and Bibler, 1991;Ritter and Bibler, 1992).…”
Section: Bioaccumulating Mercury-resistant Marine Bacteriamentioning
confidence: 99%
“…Reduction of Hg by MRB as the best such mechanism for its removal from chloralkali waste has been demonstrated (Canstein et al, 1999;Wagner-Döbler, 2003). Biosorption, another biological method involving adsorption of metals into the algal or bacterial biomass (either dead or alive), has been inexpensive and also promising (Chang and Hong, 1994;Mulligan et al, 2001), but is applicable only to low concentrations of metals in water (Chen et al, 1998). Saouter et al (1994Saouter et al ( , 1995 reported their preliminary investigation on using Hg 21 -reducing strains to decontaminate a polluted pond in Tennessee.…”
Section: Bioaccumulating Mercury-resistant Marine Bacteriamentioning
confidence: 99%
“…The dry weight of cells was determined from OD 600 using the value of 0.35 g dry weight per liter of OD 600 1.0 [13]. The Hg 2+ concentration was determined by intelligent cold vapor atom fluorescence mercuric ion measurement.…”
Section: Methodsmentioning
confidence: 99%
“…A hollow-fiber bioreactor was used in the system to retain the cells and more than 99% of mercuric ions in the wastewater were effectively accumulated. Chen and Kim realized a continuous treatment on Hg 2+ removal by recombinant E. coli in a hollow-fiber bioreactor [13]. Other researchers also set up some continuous processes to accumulate heavy metal ions with biomass [5,14,15].…”
Section: Effect Of Initial Hg 2+ Concentrationmentioning
confidence: 99%